Industrial Development and Climate Change: A Case Study of Bangladesh - Shiblee Nomani; Md. Rasel; Imran Khan Reedoy (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2022)
This study attempts to examine the climate change in Bangladesh as a cause of industrialization. Over the last few decades, pollution of the environment has become a significant concern in the case of Bangladesh. Both qualitative and quantitative data were utilized to write this article. Primary and secondary data on the environment, national policy, and technology have been gathered. Research results show that rapid and unplanned industrialization has turned into the main cause of the endangered environment. The toxic waste materials of industries are dumped into water and ground, causing air pollution, water pollution, and soil pollution. As a result, the people of the riverbank are suffering a lot. Though industrial development is very much required for a country’s development, it is also undermining the environment which will destroy the natural balance and impose a long-term effect on climate in near future. In Bangladesh, industries are developed in an unplanned and centralized way without following any particular guidelines. The poor waste management system of industries are polluting rivers and toxic emission is polluting the air as well. Natural resources are used by the industries, causing an imbalance in nature. Forests are cut down massively, which increases the chance of various natural disasters. Industrialization has a long-term effect on climate change which also increases the average temperature of the earth known as global warming. Climate change also increases the chance of various natural disasters, unemployment, food scarcity, diseases, and extinction of wildlife.